Animal Nutrition - Annual Volume 2022 [Working Title] 2021
DOI: 10.5772/intechopen.100326
|View full text |Cite
|
Sign up to set email alerts
|

Application of Vermicompost Fertilizer in Aquaculture Nutrition: Review

Abstract: Semi-intensive aquaculture using ponds is among the most common practices of fish production, whose output depends highly on the ponds’ natural primary productivity. With the increased sustainability and health concerns with artificial fish feeds and chemical fertilizers, organic manure has been credited as a cheap, safe and sustainable alternative source of aquaculture nutrition. Apart from supplying nutrients to the phytoplankton, organic manures supply food directly to zooplankton and fish, provide substrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 27 publications
(40 reference statements)
0
1
0
Order By: Relevance
“…The nutrients present in vermiwash are easily available to plants. Since, vermiwash contains high concentrations of nutrients especially ammonia, urea, nitrates and phosphates, it can be a good source to promote the growth of microalgae (Musyoka and Nairuti, 2021). While many studies have shown that microalgae can be cultivated in various wastewaters, the cultivation of microalgae in nutrient rich vermiwash has received less attention.…”
Section: Introductionmentioning
confidence: 99%
“…The nutrients present in vermiwash are easily available to plants. Since, vermiwash contains high concentrations of nutrients especially ammonia, urea, nitrates and phosphates, it can be a good source to promote the growth of microalgae (Musyoka and Nairuti, 2021). While many studies have shown that microalgae can be cultivated in various wastewaters, the cultivation of microalgae in nutrient rich vermiwash has received less attention.…”
Section: Introductionmentioning
confidence: 99%